Pengembangan E-Modul Titrasi Asam Basa Berbasis Guided Discovery Learning untuk Kelas XI SMA - Yuli, Serli Sukma; Yerimadesi, Yerimadesi (Universitas Negeri Padang, 2025)
Revolution industrial 4.0 learning is an digitalization of era, especially in the field of education so that technology-based teaching materials are needed that can increase student activity in learning. This study aims to analyze the validity, practicality and effectiveness of the acid-base titration e-module based on guided discovery learning for class XI SMA. The research method used is educational design research with a plomp model consisting of a preliminary research stage, a prototyping stage, and an assessment phase. The research subjects consisted of 8 validators, 6 people in the small group and 18 students in the field test. The research instruments used were validity questionnaires, practicality test questionnaires and student answer sheets on e-modules. Data were analyzed using Aiken's V formula and descriptive statistics. The results of the content validity test and obtained the average value of Aiken's V of 0.95 with a valid category. The results of the construct validity test and media expert validation obtained the average value of Aiken's V 0.89 in the valid category and 0.95 with the valid category. The results of the one-to-one evaluation show interesting e-modules, clear letters and easy-to-understand language. The results of data analysis in the small group test obtained an average percentage value of 87% in the very high category and 88% in the field test stage in the very high category. This data is evidenced by the ability of students to answer e-module questions at the small group stage and field test of . Based on the data analysis, it was concluded that the acid-base titration e-module based on guided discovery learning for class XI SMA was valid, practical and effective.